Assessing antibiotic residues in piglet liver and kidney samples: How to manage the results obtained. (April 2021) - Gamboa-Cruz, Carlota; Barros, Sílvia; Vila Pouca, Ana Sofia; Barbosa, Jorge; Freitas, Andreia; Ramos, Fernando
Abstract: The use of antibiotics in livestock production has become a common practice. In the EU, the use of antibiotics as growth promoters is forbidden. However, the (mis)use of antibiotics may lead to antimicrobial resistance, which adversely affects humans, animals and the environment. Thus, the present study, using a previously validated multiclass and multi-residue UHPLC-ToF-MS methodology for the determination of 43 antibiotics, presents an assessment of data obtained from 60 piglets, using their livers and kidneys as samples. Eleven antimicrobials from different families were detected, which included ciprofloxacin, danofloxacin, doxycycline, enrofloxacin, oxytetracycline, spiramycin, sulfisomidine, sulfachloropyridazine, sulfadiazine, tilmicosin, and trimethoprim. The obtained concentrations ranged from 0.3 to 438.7 μg kg −1, confirming that both kidney and liver matrices are relevant in monitoring drug residue control programs. Highlights: 11 antibiotics from 4 different families were determined in the liver and kidney samples. More than 1 antibiotic was found in 32% and 53% of the kidney and liver samples, respectively. Liver and kidney matrices, from the same animal, are relevant to residue control.